Hubungan penggunaan gadget dengan sikap tentang perubahan sistem reproduksi pubertas - Alfian Dwi Cahya; Diah Nur Annisa; Yuni Purwati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Adolescence is an important transitional phase marked by physical, psychological, and social changes, including the onset of puberty. During this period, adolescents often face various challenges in the form of emotional instability, the search for self-identity, and limited understanding of body changes and reproductive health. Purpose: To determine the relationship between gadget use and attitudes about changes in the reproductive system during puberty. Method: Quantitative research with a descriptive correlation design and a cross-sectional approach. The sample in this study used the Slovin formula and data collection techniques used purposive sampling techniques. Data analysis used univariate and bivariate analysis using the Sperm Rank test. Results: The Spearman rho correlation test between gadget use and attitudes about changes in the reproductive system during puberty obtained a correlation coefficient of 0.260 with a significance value (Sig. 2-tailed) of 0.023. Conclusion: There is a relationship between gadget use and attitudes about changes in the reproductive system during puberty.   Keywords: Attitudes About Changes In The Reproductive System; Gadget Use.   Pendahuluan: Masa remaja merupakan fase transisi penting yang ditandai oleh perubahan fisik, psikologis, dan sosial, termasuk terjadinya pubertas. Pada periode ini, remaja sering menghadapi berbagai tantangan berupa ketidakstabilan emosi, pencarian identitas diri, serta keterbatasan pemahaman mengenai perubahan tubuh dan kesehatan reproduksi. Tujuan: Untuk mengetahui hubungan penggunaan gadget dengan sikap tentang perubahan sistem reproduksi pubertas. Metode: Penelitian kuantitatif dengan desain deskriptif korelasi, dan pendekatan cross-sectional. Sample dalam penelitian ini menggunakan rumus slovin dan teknik pengambilan data menggunakan teknik purposive sampling. Analisis data menggunakan analisis univariat dan bivariat dengan menggunakan uji sperman rank. Hasil: Uji korelasi Spearman rho antara penggunaan gadget dengan sikap tentang perubahan sistem reproduksi pubertas diperoleh nilai koefisien korelasi sebesar 0.260 dengan nilai signifikansi (Sig. 2-tailed) sebesar 0.023). Simpulan: Terdapat hubungan antara penggunaan gadget dengan sikap tentang perubahan sistem reproduksi pubertas.   Kata Kunci: Penggunaan Gadget; Sikap Tentang Perubahan Sistem Reproduksi Pubertas.